A Critical Review of formulation Medhya Vati - Yadav, Sheetal; Mathur, Julee; Sharma, Anita (International Research Journal of Ayurveda & Yoga, 2024)
A multiherb formulation Medhya vati.It contains mainly four drugs, which are described for medhya properties in Charaka Chikitsha chapter 1.These drugs are described for Rasayana and medhya properties. The contents of Medhya vatiare having mainly Kashya, tikta, madhurrasa,snigdha, pichchila ,guru gunas,sheet virya andvata-pitta doshaghnata. These drugs are used to promote the Dhi, dhriti and smriti.Thesemedhya drugs have specific effect on mana and buddhi to relieve stress, anxiety and depression.